1986
DOI: 10.1093/ee/15.5.999
|View full text |Cite
|
Sign up to set email alerts
|

Degday: A Program for Calculating Degree-days, and Assumptions Behind the Degree-day Approach

Abstract: A BASIC computer program (DEGDAY) for calculating degree-days on microcomputers is presented. The program calculates heating degree-days with the rectangle, triangle, and sine wave methods and calculates cooling degree days with the sine wave method. Assumptionsand approximations associated with degree-day calculations are noted. In particular, eight factors affecting degree-days are discussed: 1) substrate availability, 2) enzyme availability, 3) approximations in laboratory estimates of development, 4) appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
192
0
24

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(219 citation statements)
references
References 18 publications
(30 reference statements)
0
192
0
24
Order By: Relevance
“…Abiotic factors, in particular, temperature can directly affect the growth of poikilotherms, such as fish (Atkinson, 1994;Kitchell et al, 1977;van der Have and de Jong, 1996) by influencing enzymatic activity, and therefore, metabolic rates (Higley et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic factors, in particular, temperature can directly affect the growth of poikilotherms, such as fish (Atkinson, 1994;Kitchell et al, 1977;van der Have and de Jong, 1996) by influencing enzymatic activity, and therefore, metabolic rates (Higley et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Embora a previsão de ocorrência, com base na temperatura do solo, tenha diferido da época observada, os erros foram de apenas 10,1 e 12,2%, considerando-se, respectivamente, as temperaturas registradas e estimadas (Tabela 2). Segundo Higley et al (1986), esta margem de erro é tolerável, já que em modelos de graus-dia que possibilitem previsões de ocorrência com 10% a 15% de imprecisão são ainda considerados adequados para a tomada de decisão no manejo de pragas. Com base nesse princípio, pode-se afirmar que as temperaturas do solo (registradas ou estimadas) podem ser utilizadas para prever a ocorrência de D. speciosa, utilizando o modelo de graus-dia de laboratório, enquanto a temperatura do ar não se adequaria para tal previsão.…”
Section: Resultsunclassified
“…In fact, the occurrence of arthropods under field conditions may be observed before or after the predicted date, and these differences may be associated with errors in the lower temperature threshold (Tb) and thermal constant (k) estimates. Thus, degree-day models are considered adequate to be used in pest management programs if they predict the occurrence of a pest within a margin of error of up to two days (MORALES; HOWER, 1981, WEST;LAING, 1984, HIGLEY et al, 1986CIVIDANES;BERNAL;GONZÁLEZ, 1993;FIGUEIREDO, 1997). Ávila et al (2002) observed that degree-day values accumulated during development of the coleopteran Diabrotica speciosa (Chrysomelidae), an agricultural pest, under field conditions, due to fluctuating soil and air temperatures were different from values obtained in the laboratory conditions where constant temperatures were used.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies, in degree-days, have aided the development of models, which have been used in Integrated Pest Management programs, so as to predict the occurrence of population peaks under field conditions, and determine the most adequate period for sampling and control measures, providing a better understanding about population dynamics of pest insects and their natural enemies (WEST;LAING, 1984;HIGLEY et al, 1986;MILLER, 1992).…”
Section: Introductionmentioning
confidence: 99%